Host country attractiveness for CDM non-sink projects - Martina Jung (Hamburg Institute of International Economics (HWWA), 2005)
In the present study, CDM host countries are classified according to their attractiveness for CDM non-sink projects. A cluster analysis is conducted based on three different factors determining host country attractiveness (mitigation potential, institutional CDM capacity and general investment climate) in order to elaborate a CDM host country classification. The results suggest that only a small proportion of potential host countries will attract most of the CDM investment. The CDM (non-sink) stars are China, India, Brazil, Argentina, Mexico, South Africa, Indonesia and Thailand. They are followed by attractive countries like Costa Rica, Trinidad and Tobago, Mongolia, Panama, and Chile. While most of the promising CDM host countries are located in Latin America and Asia, the general attractiveness of African host countries is relatively low (with the exception of South Africa). Policy implications of this rather inequitable geographical distribution of CDM project activities are discussed briefly.
Keywords: Q25; C49; 330; Clean development mechanism; Kyoto Protocol; attractiveness; cluster analysis; Clean Development Mechanism; Klimaschutz; Entwicklungsprojekt; Entwicklungsländer; Lateinamerika; Asien; Afrika